Theoretical and experimental spectroscopic studies, XPS analysis, dimer interaction energies and molecular docking study of 5-(adamantan-1-yl)-N-methyl-1, 3, 4-thiadiazol-2-amine. (December 2019) - Al-Wahaibi, Lamya H.; Sert, Yusuf; Ucun, Fatih; Al-Shaalan, Nora H.; Alsfouk, Aisha; El-Emam, Ali A.; Karakaya, Mustafa
Abstract: This research relates to the molecular structure, electronic properties and IR, Raman and XPS analyses of the potential chemotherapeutic agent namely, 5-(adamantan-1-yl)- N -methyl-1, 3, 4-thiadiazol-2-amine. Another purpose is to explore the structural stabilities and consistencies and, to assess the stable interaction energy and intermolecular hydrogen bond geometry for its dimeric structure. The monomer and dimer optimizations of the molecule have been calculated by the DFT method using various functionals such as B3LYP, B3PW91, mPW1PW91 and M06-2X. Although the minimum energy optimization was calculated at the B3LYP functional, the BSSE-corrected and uncorrected interaction energies of the dimer structure were more effectively obtained with the M062X functional. This assured us a test of the efficiency of M06-Class functional calculations on intermolecular interactions of strongly bound systems. Additionally, the molecular docking study was done between our molecule (ligand) and the previously studied and known as cortisone reductase 11β-Hydroxysteroid dehydrogenase type 1 (receptor, 11-β-HSD1: PDB-2ILT). Graphical abstract: Image 1 Highlights: Experimental IR, Raman and XPS spectral analysis have been performed. Monomer and dimer optimizations of investigated compound have been performed in DFT with various functional approaches. Minimum energy optimizations, stable interaction energies and binding abilities have been assessed on dimer structure. Energy gaps and views of frontier molecular orbitals have been interpreted by partial densities of states spectral analysis. Molecular docking study have been carried out.